P96 Fertility outcome after fertility-sparing surgery of malignant ovarian germ cell tumour. (1st November 2019) - Bouyou, J; Bentivegna, E; Maulard, A; Pautier, P; Genestie, C; Gouy, S; Morice, P
Abstract : Introduction/Background: Malignant ovarian germ cell tumours (MOGCT) are the most frequent cancer among women below 20 years old. These rare ovarian tumours have a great sensitivity to platinum-based chemotherapy and nowadays the conservative surgical management is the standard protocol. The aim of this study is to analyse the fertility outcome after conservative treatment of women with malignant ovarian germ cell tumour. Methodology: We included retrospectively childbearing women with MOGCT who underwent fertility-sparing surgery in our institution between 1995 and 2016. Results: Seventy patients with MOGCT met the inclusion criteria. The median age was 18 years old and 91, 4% of the patients were nulliparous. The median follow-up duration was 8, 8 years. Most of patients have a Mixed Tumour (n=27, 38.6%) and FIGO stage was I in in 42 patients (60%), II in 5 patients (7%), III in 17 patients (23%), IV in 5 patients (7%). Only five (7%) patients have neoadjuvant chemotherapy and the majority of patients have adjuvant chemotherapy (n=59, 84%). We report 14 recurrences for 69 ( 20%). We have lost of sight 12 patients after treatment for which we have no data about fertility. Twenty-one patients had no fertility desire after treatment in the study period. Thirty seven patients attempted pregnancy and 30 of them (81%) became pregnant. We report 55 pregnancies with 43 childbirths. The average time to obtain a pregnancy was 4.3 years after the diagnosis of a MOGCT. Three patients went through assisted reproductive technique, two had a successful pregnancy. Conclusion: Patients treated for a MOGCT can expect to retain a subsequent fertility and become pregnant after fertility sparing surgery. The techniques for preserving fertility even though they are still rarely suggested nowadays in patients with MOGCT, could increase the amount of pregnancies for patients who wish for it. Disclosure: Nothing to disclose.